2019
DOI: 10.4209/aaqr.2019.06.0304
|View full text |Cite
|
Sign up to set email alerts
|

Emission Factors of NOx, SO2, PM and VOCs in Pharmaceuticals, Brick and Food Industries in Shanxi, China

Abstract: The acquisition of accurate emission factors (EFs) of pollutants is an inevitable step to the establishment of emission inventories for development of pollution control policies. The current studies were focused on large-scale industries (LSIs) although tremendous pollutants emitted from the small-scale industries (SSIs) with small coal-fired boilers (SCFBs) ascribe to the deficiency of pollutant removal facilities (RFs). A systematic field sampling and measurements conducted in 51 enterprises involving produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Cu was the main component in wire, which caused the high level of Cu in PM 2.5 from WCC. HMs and As were more concerned than the other elements in their seriously adverse health effects to people (Li et al, 2017a, b;Hu et al, 2019). In this study, the 10 HMs (e.g., Zn, Mn, Cu, Pb, Co, Ni, V, Cr, Cd, Sn) and As most concerned were all detected.…”
Section: Concentrations and Exposure Risks Of Inorganic Elementssupporting
confidence: 51%
See 1 more Smart Citation
“…Cu was the main component in wire, which caused the high level of Cu in PM 2.5 from WCC. HMs and As were more concerned than the other elements in their seriously adverse health effects to people (Li et al, 2017a, b;Hu et al, 2019). In this study, the 10 HMs (e.g., Zn, Mn, Cu, Pb, Co, Ni, V, Cr, Cd, Sn) and As most concerned were all detected.…”
Section: Concentrations and Exposure Risks Of Inorganic Elementssupporting
confidence: 51%
“…Serious atmospheric quality deterioration has occurred in rapidly developing China (Fang et al, 2009;Pascal et al, 2013;Li et al, 2017a;Hu et al, 2019;. Zhai et al (2019) reported that PM 2.5 should responsible for 1.1 × 10 6 excess deaths in 2015 in China.…”
Section: Introductionmentioning
confidence: 99%
“…Pearson correlation analysis was performed using OriginPro 8.0 software (OriginLab Corporation). Differences were considered statistically significant at p < 0.05 (Hu et al, 2019; B. Liu, Wu, et al, 2017; Perrone et al, 2010; M. Song, Liu, Zhang, et al, 2019; Y. Wang et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Therein, NO accounts for the majority of NOx (Anthonysamy et al, 2018;Wu et al, 2022). It pollutes the air and directly affects humans, animals, and plants (Harikrishnan et al, 2005;Hu et al, 2019;Wang et al, 2022). Therefore, the discovery and development of NO treatment technologies are of great interest to scientists and engineers (Chou et al, 2022).…”
Section: Introductionmentioning
confidence: 99%